MALL in the Wild: How Indonesian EFL Learners Self-Regulate Vocabulary Acquisition Through App-Based Learning Outside the Classroom - Mulia (Journal of Innovation in English Education and Language Teaching, 2026)
Mobile-Assisted Language Learning (MALL) has been studied extensively in formal instructional contexts, but far less is known about how EFL learners deploy mobile vocabulary apps in the unstructured, self-directed conditions of out-of-class learning—what this study calls MALL in the wild. Drawing on ecological momentary assessment, learning diaries, and in-depth interviews with twenty-two Indonesian EFL learners at a public Islamic university in Aceh over sixteen weeks, this study investigates the self-regulatory processes through which learners initiate, sustain, and abandon mobile vocabulary app use outside the classroom. Findings reveal that out-of-class MALL engagement is shaped by a dynamic interplay of situational triggers, motivational beliefs, goal specificity, and the degree to which app design affords or constrains self-regulatory behaviour. Four learner profiles emerged: disciplined self-schedulers, opportunistic engagers, anxiety-driven users, and gradual abandoners. Disciplined self-schedulers showed the strongest vocabulary gains; gradual abandoners showed minimal gains despite initial enthusiasm. The study draws on Self-Regulation Theory (Zimmerman, 2000) and ecological perspectives on language learning (van Lier, 2004) to argue that MALL's potential for supporting vocabulary development outside the classroom is substantially mediated by learners' self-regulatory capacities—and that app design and course integration strategies need to be explicitly oriented towards building those capacities rather than assuming they exist.